Princess Posey and the Monster Stew - Greene, Stephanie; Sisson, Stephanie Roth (New York : G. P. Putnam's Sons, 2012)
First-grader Posey and her friends are excited about Halloween, but also a little nervous about trick-or-treating and eating Miss Lee's monster stew.
Keywords: Halloween -- Fiction; Teachers -- Fiction; Friendship -- Fiction; School stories